Healthsaving activity of comprehensive educational establishments' leaders as psychological and pedagogical problem - O.V. Gres (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to show the essence and structural components of healthsaving activity of comprehensive educational establishments' leader. Material: conducted an analysis of psychological and pedagogical sources. Results: healthsaving activity of comprehensive educational establishments' leader was conducted. An integral part of leader's management-pedagogical activity directed on creation of healthy environment (physical-subjective, psychological-communicative, educational) of educational establishment. Also floating, saving and strengthening of health of all participants (pupils, pedagogues, parents) of pedagogical process. It was analysed contents of main components (planning, organization, stimulation, control) of healthsaving activity of leader. Conclusions: constant pedagogical monitoring allows to estimate an effectiveness of educational work of establishment according to the degree of achievement of assigned tasks and to make corresponding corrections in a decision of healthsaving questions of pedagogical process participants.